4-tert-Butyl-N-[(2,6-dimethylphenyl)carbamothioyl]benzamide - Yusof, M. Sukeri M. (International Union of Crystallography, 2012)
The asymmetric unit of the title compound, C(20)H(24)N(2)OS, consists of two crystallographically independent molecules. In each molecule, an intramolecular N—H⋯O hydrogen bond forms an S(6) ring motif. The dihedral angles between the terminal benzene rings in the two molecules are 75.52 (7) and 42.80 (7)°. In the crystal, intermolecular N—H⋯S interactions link the molecules into a chain along the c axis.